?-ALMOST DIFFERENCE SEQUENCES OF FUZZY NUMBERS - Altin, Yavuz (Ankara Univ, Fac Sci, 2016)
In this study, we introduce several sets of sequences of fuzzy numbers using various sequences lambda and mu in the class A and examine some inclusionrelations among these sets.
Keywords: Fuzzy number; difference sequence; statistical convergence